Nesting Behavior of Abispa ephippium (Fabricius) (Hymenoptera: Vespidae: Eumeninae): Extended Parental Care in an Australian Mason Wasp - Robert W. Matthews; Janice R. Matthews (Psyche: A Journal of Entomology)
The genus Abispa includes Australia's largest wasps, potters with distinctive mud nests weighing up to 0.5 kg. During 31 days near Katherine, NT, Australia, we observed 8 active A. ephippium (Fabricius) nests and dissected 16. Nesting is lengthy and asynchronous; female generations often overlap. Females display long-term parental care through truncated progressive provisioning, removing debris, repairing damage, and attacking potential invaders. Males patrol water-gathering spots, and visit and associate with active nests, mating there and in flight. Females actively guard nests, but challenged nest-attending males simply retreat. The distinctive funnel-shaped entrance helps females defend nests physically but probably not chemically; dismantled for cell closure material, it is built anew for each cell. Nests contain up to 8 cells; construction and provisioning total about 7 days per cell. The only parasite was Stilbum cyanurum Forster. Thievery and nest usurpation by Pseudabispa paragioides (Meade-Waldo) were discovered.